Overexpression of LINC00936 Inhibits the Proliferation and Invasion of Endometrial Carcinoma Cells. (31st May 2022) - Sun, Haizhu; Li, Peiling
Abstract : Objective . Endometrial carcinoma (EC) is one of the most common malignancies leading to death in women and poses a serious threat to women's health. Therefore, exploring the molecular mechanisms affecting EC progression and metastasis is a clinical research hotspot. It has been shown that lncRNAs play an important role in the pathogenesis of EC. It is important to investigate the role of lncRNAs in the growth of EC to improve diagnosis and find new therapeutic targets of EC. Methods . The expression of LINC00936 in 36 EC tissues, paracancerous tissues, and cell lines was measured by fluorescence quantitative PCR. The relationship between LINC00936 expression and clinicopathological characteristics of patients was analyzed. The effects of overexpression of LINC00936 on proliferation, invasion, and migration of EC cells were examined by CCK-8 and transwell assays. Colony formation assay was also performed to evaluate the colony forming ability of EC cells. The effect of overexpression of LINC00936 on the expression of EMT-related proteins in EC cells was examined by western blot. In addition, the effect of LINC00936 overexpression on the growth of EC in vivo was examined by using tumorigenicity assay in the nude mouse. Results . LINC00936 was expressed at a low level in EC tissues and cell lines and significantly correlated with tumor size and lymphatic metastasis of patients. Overexpression of LINC00936 significantly inhibited the proliferation, invasion, and migration, as well as colony formation ability of EC cells. Western blot analysis showed that overexpression of LINC00936 significantly promoted the expression of E-cadherin and inhibited the expression of N-cadherin and vimentin in EC cells. Tumorigenic assays in the nude mouse demonstrated that overexpression of LINC00936 inhibited the growth of EC in vivo by suppressing Ki-67 and promoting E-cadherin expression. Conclusion . LINC00936 was expressed at a low level in EC tissues and significantly correlated with tumor size and lymphatic metastasis of patients. Overexpression of LINC00936 significantly inhibited the proliferation, invasion, and migration, as well as colony formation ability of EC cells. Therefore, LINC00936 could be a new target for the early diagnosis and treatment of EC patients.